Digitalisation, innovation, and industrial organisation: the pivotal case of the auto industry. (1st September 2004) - Bomsel, Olivier; Le Blanc, Gilles
This paper considers the economics of digitalisation, defined as the digital coding of information and the growing productivity gains in processing and transmission it enables. It examines the effects of this process on existing models of the firm, industry structure and innovation. The diffusion and adoption of digital innovations are then illustrated by the example of the automobile industry. This sector offers instructive insights since it played a crucial role in the history of industrial innovation and competitive business models.